Relatório de Estágio Profissional "Aprendizagens e desafios de uma professora estagiária" - Filipa Daniela Vieira Miranda (2018)
The following internship report comes within the framework of the subject concerning the professional traineeship. This subject is a key element in the study plans of the 2nd term of the major in Physical Education Teaching in Primary and Secundary Schools of the Faculty of Sports of the University of Porto. This document reflects the practice of a supervised traineeship which happened in the school year of 2017/2018 in a school in Vila Nova de Gaia. Therefore, this document reflects the final thoughts concerning the professional practice experience, emphasising the teaching-learning process. The teaching-learning process was enabled by a intensive literature research as well by personal experiences during the whole traineeship. It is important to enhance that the time frame in which we assume the role of a Physical Education, teacher is astonishingly enriching, and it is a constant learning experience. Bearing in mind the importance of the traineeship, we were helped and supervised by a cooperative teacher from the school we were working with, as well as by a orienting teacher that guides us to the best of his abilities. The obstacles of being a teacher have proven to be much more challenging than I initially anticiped. Hence the tough path I had to face. However, the hardship are a part of being a teacher. On that account I tried to mention not only the victories I conquered and the milestones I reached, but also all the mistakes and difficulties I endured during the last year. Furthermore the document was divided in four parts: (1) the first one is the biographic framing, (2) the second one concerns the framing of the professional practice, (3) the third one addresses the fulfillment of the professional practice and it is, once again divided in three sections: the organization of the teaching-learning process, the relationships between the school and the overall community and the professional development, and lastly, (4) the fourth is the conclusion and the overall future perspectives. In summary this was a year full of learning experiences, but I am aware that this is only the end of a chapter and that I have many more challenges yet to come.